Evaluation of the phagocitary capacity of the mononuclear system in an experimental model of obstructive jaundice employing Tc- 99m Escherichia coli - Diniz,Simone Odília Fernandes (2005)
Infections and endotoxemia continue to be the principal causes of morbidity and mortality of patients with obstructions of the bile duct. The objective of the present work was the investigation of the phagocitary capacity of the mononuclear system in an experimental model of obstructive jaundice utilizing Tc-99m E.coli. The levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) were significantly higher in jaundiced rats than in the control animals (p < 0.001). The liver of the jaundiced animals presented a significant reduction in Tc-99m E.coli uptake when compared to the controls (p < 0.001). The data also showed that there was a significant increase in the uptake of Tc-99m E.coli by the lungs of jaundiced rats (p < 0.01). The histological analyses of the liver of jaundiced rats showed an intense and diffuse proliferation of the bile ducts and an intensified polyploidy of the hepatocytes (mean volume = 843 µm³), but no significant alterations were observed in the lungs of either group. This dates could contribute to a better understanding of the mechanisms involved in cases of bacteremia, renal failure and pulmonary dysfunction observed in clinical analyses of obstructive jaundice.